“You Want Them Pretty, but Not Too Intelligent!”: Everyday Talk and the Continuum of Men's Violence Against Women in Forensic Institutional Care - Joyes, Emma C.; Jordan, Mel (Frontiers in Psychiatry, 2022)
This paper analyses ethnographic data from an inpatient forensic mental health hospital in the UK. Ethnographic fieldwork occurred over 300 hours – overtly participating in, exploring, and recording the daily life of the community. Our central argument is that the intertwining and interdependent cultural and custodial elements of forensic healthcare environments are integral and influential to care, culture, and conduct within such institutions—including concerning misogynistic everyday talk and the continuum of men’s violence against women therein. The forensic setting houses persons with offence convictions who are also in receipt of ongoing mental healthcare – a criminal justice system and healthcare meeting-point. This context, whilst laden with interpersonal and institutional difficulties unique to a secure context that must provide care and custody concurrently, is also a continuation of contemporary social issues experienced within community life, as the boundaries of such institutions are porous – polis values traverse physical brickwork. Salient issues include heteronormative gender roles, hegemonic masculinity, and misogynistic ways-of-being. This paper embraces a feminist lens to explore everyday social interactions, forensic setting talk, and the embodied experience of the female ethnographer within a male-dominated forensic setting. We contribute to the literature by newly theorising the influences of hierarchical heterosexual gender roles, violent language in forensic settings, and misogynistic attitudes and practice, on the care for, and rehabilitation of, patients. This paper presents five excerpts of ethnographic data which evidence the gendered ward environment and highlight a series of encounters pertaining to problematic social life, which are argued to be rooted in patriarchal views of women. These views are problematised within the sexual offending rehabilitative context by considering the clinical risk associated. Further, we argue that to only focus on the most violent and severe end of the continuum ignores a pervasive cultural landscape of the polis in wider community, beyond the institution, that facilitates the more commonly experienced end of the continuum related to misogynistic values, encounters, and talk, and thus we evidence how social norms and habitualised gendered actions are condusive of men’s violence more broadly – inside and outside the hospital.